Tramas e dramas da maternidade na adolescência: gênero, poder e cultura (Uberlândia 2000-2010) - Giuliani, Carla Denari (2012)
He adult life was altered very much in the western modern societies. The redimensionamento of the parental authority, new educative standards, transformations in the relations of type and between generations they compose new social and familiar scenery. We bring modernpowders or pluralist near to the century XXI with the family, to the individualism and the relations descompromissada. In this slant when we think about our object of study: of making pregnant of adolescents in the century XXI, after the revolution of the pill and of the birth of the feminism, the act turns clear thinking which sense has this motherhood in this time of fluidity, ephemerality of the individual one, of the contemporary culture that puts languages, paradigms and projects on top. Which sense has this counter-power practised by them when they are opposed to the public politics and to a model established by the contemporary society, which translates the pregnancy in the adolescence like a problem and or I wander. This study was developed from written and oral fountains obtained with interviews you give adolescent pregnant women his companions and, when MG was located in the city of Uberlândia, We Notice his families that in spite of the thought \"hegemônico\", of mistake or problem translated by the media, by the programs of health, by the medical teaching itself, and for the contemporary world, the persons hold out and rewrite new judgements of values.